Possible functional role of olfactory subsystems in monitoring inhalation and exhalation - Mori, Kensaku; Manabe, Hiroyuki; Narikiyo, Kimiya (Frontiers in neuroanatomy, 2014)
Olfactory perception occurs in discrete breaths (sniffs). [...]respiration rhythm plays a key role orchestrating the information processing mode across a number of regions in the central olfactory system, which includes the olfactory bulb and numerous areas of the olfactory cortex (Mori and Manabe, 2014). During the inhalation phase, odorants in the external world are drawn, together with external cool air, into the nasal cavity and thereby activate olfactory sensory neurons in the olfactory epithelium. [...]the central olfactory system is engaged in the processing of olfactory sensory inputs from the external world during the inhalation phase. [...]a unique mode of olfactory sensory neuron stimulation occurs during eating: the central olfactory system receives retronasal odor stimulation from foods in the mouth during the exhalation phase (Gautam and Verhagen, 2012). [...]in awake behaving states, the central olfactory system appears subject to respiration phase-paced changes in information processing mode. The timing of inhalation and exhalation plays a pivotal role in information processing in the central olfactory system (Mori et al., 2013; Nagayama et al., 2014). [...]our understanding of the dynamics of information processing in the large-scale networks of the central olfactory system is critically dependent on a better understanding of neuronal mechanisms for detecting respiratory phases, and for sending breath cycle signals to specific glomeruli in the olfactory bulb.